Preoperative Diagnosis of Thyroid Follicular Tumor - Ye Beibei, Zhang Yifeng (Advanced Ultrasound in Diagnosis and Therapy)
The incidence rate of follicular thyroid carcinoma ranks second among thyroid malignancies. Compared to papillary thyroid carcinoma, it has higher rates of recurrence and metastasis, making it a threat to a patient's health. Unfortunately, accurately diagnosing follicular tumors before surgery remains an unresolved issue, as this type of disease is a gray area of fine-needle aspiration biopsy and can be challenging to differentiate clinically from benign thyroid follicular tumors. There are many studies have focused on the preoperative diagnosis of follicular tumors, and much progress has been made. However, according to current research, postoperative biopsies are still the only definitive ways to diagnose follicular thyroid carcinoma, providing evidence of capsule and vascular infiltration. We must emphasize the importance of early detection and diagnosis of follicular thyroid carcinoma to ensure effective treatment and recovery. This review provides a comprehensive summary of the literature on follicular thyroid carcinoma, including its epidemiology, clinical features, imaging diagnosis, genetic and molecular testing of thyroid follicular carcinoma, and a detailed description of the preoperative diagnosis of follicular thyroid carcinoma. We urge medical professionals to use this information to improve their understanding of this disease and enhance their ability to accurately diagnose and treat it.